Facing the Monsters: Protestant Antisemitism in Readings of Jonah - Decker, Hans (Hebrew bible and ancient Israel, 2025)
This article examines the ethical implications of antisemitic readings of the book of Jonah for current interpretation. It begins with Martin Luther's interpretation, which presents the story as an enactment of divine anti-Judaism that condemns Jonah and upholds the Ninevites' repentance as an archetypal expression of sola fide. The article then explores alternative frameworks for theological reading, reinterpreting the Protestant identification with Nineveh in terms of Nineveh's role in the Assyrian conquest. The possibilities that emerge suggest different theological and ethical implications for the Protestant reading tradition, raising challenging questions about divine mercy and human salvation that remain unresolved, in keeping with the narrative ambiguities of Jonah. The long history of antisemitism in biblical scholarship imbues interpretation with ethical weight that cannot be responsibly ignored. This article suggests a hopeful way forward through ethical reading, rejecting the triumphal supersessionist approach to Jonah in favour of a hermeneutic of humility.